2009
DOI: 10.1021/la803431k
|View full text |Cite
|
Sign up to set email alerts
|

Optical Characterization of Asphaltenes at the Air−Water Interface

Abstract: Asphaltenes extracted from Arabian light crude oil have been investigated at the air-water interface of a Langmuir trough by in situ optical techniques. Brewster angle microscopy (BAM) and reflection spectroscopy have been used to extract new information about the microscopic organization of the asphaltene films in terms of association phenomena and chromophore orientation, respectively. The use of different spreading concentrations in the range 0.1-15 mg mL-1 reveals significant changes in the behavior at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
53
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 42 publications
16
53
2
2
Order By: Relevance
“…5), in agreement with previously published data [60][61][62] . In previous studies the morphology of asphaltene films was probed in situ with BAM at the air-water interface 41,[60][61][62] , while asphaltenes films at the toluene-water interface have been previously imaged after being transferred onto solid substrates (LB films) 55,57,63 . In the current study, after the toluene (good solvent) top phase was gently added, the cracks in the film were observed to "heal" (Fig.…”
Section: Morphology Of the Films At Toluene-water Interfacesupporting
confidence: 92%
“…5), in agreement with previously published data [60][61][62] . In previous studies the morphology of asphaltene films was probed in situ with BAM at the air-water interface 41,[60][61][62] , while asphaltenes films at the toluene-water interface have been previously imaged after being transferred onto solid substrates (LB films) 55,57,63 . In the current study, after the toluene (good solvent) top phase was gently added, the cracks in the film were observed to "heal" (Fig.…”
Section: Morphology Of the Films At Toluene-water Interfacesupporting
confidence: 92%
“…22 The nanoaggregate to cluster transition with increasing concentration has also been indicated in interfacial studies. 23 The "island" 1.5 nm molecular architecture depicted in Fig. 2 with a single polycyclic aromatic hydrocarbon (PAH) per molecule previously proposed by time resolved fluorescence polarization studies [24][25] has been confirmed by laser desorption, laser ionization mass spectrometry (L 2 MS).…”
Section: Flory-huggins-zuo Model For Asphaltene Equilibrium Distributmentioning
confidence: 63%
“…Nanoaggregates were observed using high-Q ultrasonics [17,18], NMR (nuclear magnetic resonance) [19], DC-conductivity [20,21], SANS (small-angle neutron scattering) and SAXS (small-angle X-ray scattering) [22], and centrifugation [23,24], along with related analysis of gravity gradients in oil reservoirs [25] among other techniques. Clusters were observed by flocculation kinetics [26,27], interfacial studies [28], and DC-conductivity [20].…”
Section: Introductionmentioning
confidence: 99%